Profesor Halina Evert-Kappesowa i Madame Dupont - Dąbrowska, Małgorzata (Przegląd Nauk Historycznych, 2013)
Halina Evert-Kappesowa was a professor of Byzantine studies at the University of Łódź. She was born in the family of Ludwik Evert, a publisher and a senator in the Polish Parliament before WW2. She led a cushioned existence as the wife of Alfons Kappes, an entrepreneur and a representative of Polish industry in Turkey. They spent some years in Istambul where she followed the traces of old Constantinople. Due to her Turkish experience she became interested in the history and culture of the Byzantine Empire. She entered the University of Warsaw and studied the history of Byzantium under Professors Oskar Halecki and Kazimierz Zakrzewski. WW2 and then the communist system introduced to Poland in 1945 changed her life completely. She settled down in Łódź, but found it difficult to find a job at the University because of her social background. The questionnaires at the University Archives show how discreet she was when describing the vicissitudes of her family and to how she tried to adjust to the new political system. Malgorzata Dabrowska recreates Professor Kappesowa’s difficult scholarly career in the years 1945–1985. The article is based not only on the University documents but mostly on the private correspondence with Dr Muriel Heppell, whom Halina Evert- Kappesowa met during her stay in Dumbarton Oaks, a famous Center of Byzantine Studies in Washington D.C. This exchange of letters shows the hidden thoughts of a kind lady, who never accepted the postwar order and was depressed in her scholarly and private life. Humiliated by the living conditions, she found an unexpected support in Madame Dupont, a mysterious person who appears in the letters as a financial benefactress of her travels to the libraries in the West, still difficult to reach in the seventies for the lady who remembered the fortune of the Evert family.